2012
DOI: 10.1146/annurev-physiol-020911-153333
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in Diabetic Disease Models: The Tubular System in the Pathophysiology of the Diabetic Kidney

Abstract: Diabetes mellitus affects the kidney in stages. At the onset of diabetes mellitus, in a subset of diabetic patients the kidneys grow large, and glomerular filtration rate (GFR) becomes supranormal, which are risk factors for developing diabetic nephropathy later in life. This review outlines a pathophysiological concept that focuses on the tubular system to explain these changes. The concept includes the tubular hypothesis of glomerular filtration, which states that early tubular growth and sodium-glucose cotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
267
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(283 citation statements)
references
References 146 publications
(210 reference statements)
10
267
0
6
Order By: Relevance
“…This is likely to be based on: (1) hyperglycaemiainduced increases in nitric oxide and vasodilatory prostanoid bioactivity in the pre-glomerular, afferent renal circulation [11,13,24]; (2) changes in tubuloglomerular feedback, due to increased sodium-glucose co-transport at the proximal tubule. Increased proximal tubular sodium reabsorption decreases distal delivery to the macula densa, resulting in afferent vasodilatation [28]. Since hyperfiltration, used as a surrogate for intraglomerular pressure in humans, also contributes to the initiation of diabetic nephropathy in some but not all studies [10,29], we hypothesised that DM-H patients would also exhibit increased urinary excretion of inflammatory mediators that have been linked with kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be based on: (1) hyperglycaemiainduced increases in nitric oxide and vasodilatory prostanoid bioactivity in the pre-glomerular, afferent renal circulation [11,13,24]; (2) changes in tubuloglomerular feedback, due to increased sodium-glucose co-transport at the proximal tubule. Increased proximal tubular sodium reabsorption decreases distal delivery to the macula densa, resulting in afferent vasodilatation [28]. Since hyperfiltration, used as a surrogate for intraglomerular pressure in humans, also contributes to the initiation of diabetic nephropathy in some but not all studies [10,29], we hypothesised that DM-H patients would also exhibit increased urinary excretion of inflammatory mediators that have been linked with kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although DN was traditionally considered a primarily glomerular disease, accumulating evidence indicates that renal tubules play an important role in the pathogenesis of DN (1)(2)(3). However, the mechanisms through which the deregulation of renal tubules contributes to the development of DN remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The downregulation of SnoN expression in human renal proximal tubule epithelial cells under high-glucose conditions is mediated by an increase in Smurf2 expression through TGF-β1 signaling XIUJI LI 1,3 , ZONGLI DIAO 1 , JIAXIANG DING 1 , RUIXIA LIU 2 , LIYAN WANG 1 , WEN HUANG 3 and WENHU LIU rats and primary proximal tubule epithelial cells under highglucose conditions (13). Moreover, we demonstrated that SnoN inhibited high-glucose-induced epithelial-mesenchymal transition (EMT) in renal tubule cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…A recent emphasis is placed on the role of the tubulointerstitium in kidney disease, and its contribution to both initial events perturbing kidney function, but also in sustaining renal injury. [10][11][12] A tubular hypothesis whereby PT growth promotes PT hyper-reabsorption, which in turn contributes to hyperfiltration and hypertension, leading to further renal injury, is now given significant recognition in the literature (reviewed in Vallon and Thomson 12 ). Transforming growth factor beta (TGFβ) is a key regulator of PT changes, promoting and maintaining alterations in growth and fibrotic responses.…”
mentioning
confidence: 99%